2004
DOI: 10.1038/nn1278
|View full text |Cite
|
Sign up to set email alerts
|

Underlying principles of visual shape selectivity in posterior inferotemporal cortex

Abstract: Object perception depends on shape processing in the ventral visual pathway, which in monkeys culminates in inferotemporal cortex (IT). Here we provide a description of fundamental quantitative principles governing neural selectivity for complex shape in IT. By measuring responses to large, parametric sets of two-dimensional (2D) silhouette shapes, we found that neurons in posterior IT (Brodmann's areas TEO and posterior TE) integrate information about multiple contour elements (straight and curved edge fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
308
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(345 citation statements)
references
References 48 publications
30
308
7
Order By: Relevance
“…Network depth ranged from one to three layers, and filter weights for each layer were chosen randomly from bounded uniform distributions whose bounds were model parameters (SI Text). These models are consistent with the Hierarchical Linear-Nonlinear (HLN) hypothesis that higher level neurons (e.g., IT) output a linear weighting of inputs from intermediate-level (e.g., V4) neurons followed by simple additional nonlinearities (14,16,29).…”
Section: Resultssupporting
confidence: 80%
“…Network depth ranged from one to three layers, and filter weights for each layer were chosen randomly from bounded uniform distributions whose bounds were model parameters (SI Text). These models are consistent with the Hierarchical Linear-Nonlinear (HLN) hypothesis that higher level neurons (e.g., IT) output a linear weighting of inputs from intermediate-level (e.g., V4) neurons followed by simple additional nonlinearities (14,16,29).…”
Section: Resultssupporting
confidence: 80%
“…A different study (25) recorded neuronal responses to complex shapes in TEO and/or posterior TE, where we found MCP to be located. These stimuli were 2D line drawings composed of straight lines and curved components.…”
Section: Discussionmentioning
confidence: 67%
“…4). Furthermore, it has been shown that single cells and columns in the monkey IT cortex are selective for moderately complex features 96,97 ; that neurons in v4 and in the posterior IT cortex are tuned for simple shape characteristics 98,99 ; and that IT neurons exhibit gradual tuning in simple shape spaces 50,51 . Finally, single-cell recordings and fMRI studies have provided evidence of selectivity for object parts and non-accidental properties (for example, symmetry, parallelism and collinearity) in the ventral temporal cortex 49,100 , as predicted by structural description theories of object recognition 101,102 .…”
Section: Basic Properties In the Ventral Visual Cortexmentioning
confidence: 99%